Sustainability Model of Accurate Accounting Software Implementation for Outcome-Based Education in Higher Education - Sidauruk , Sri Hartati; Rizkian, Muhammad Saleh; Sari , Devi Purnama (International Journal of Multidisciplinary Sciences and Arts, 2026)
The implementation of Outcome-Based Education (OBE) in higher education requires a learning process oriented towards achieving graduate competencies, including mastery of digital accounting skills. Accurate Accounting System software is one of the accounting applications widely used in industrial practice, and its potential for integration into OBE-based learning is significant. This study aims to analyze the factors that influence the sustainability of Accurate implementation and develop a conceptual model for the software's continued use in supporting OBE implementation. This study uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents consisting of students, lecturers, and educational staff who use Accurate. The variables analyzed include the Technology Readiness Index (TRI), the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and the Sustainability of Implementation Model. Data were analyzed using SPSS through validity and reliability tests, as well as multiple linear regression. The results showed that optimism and innovation had a significant positive effect on performance expectancy (? = 0.45, p < 0.01) and effort expectancy (? = 0.38, p < 0.05). Conversely, discomfort and insecurity had a negative effect on effort expectancy (? = -0.33, p < 0.05) and behavioral intention (? = -0.29, p < 0.05). This indicates that technological readiness (TRI) has an indirect effect on implementation sustainability through the UTAUT variable. This study strengthens the view that psychological readiness of technology users is an important prerequisite for educational technology adoption.